Dynamics of the genetic diversity of oat varieties in the Tyumen region at avenin-coding loci - A. V. Lyubimova; G. V. Tobolova; D. I. Eremin; I. G. Loskutov (Вавиловский журнал генетики и селекции)
Molecular and biochemical markers are used to analyze the intraspecific genetic diversity of crops.  Prolamincoding loci are highly effective for assessing this indicator. On the basis of the Laboratory of Varietal  Seed Identification of the State Agrarian University of the Northern Trans-Urals, 18 varieties of common oat  included in the State Register of Selection Achievements in the Tyumen Region from the 1930s to 2019 were  studied by electrophoresis in 2018–2019. The aim of the work was to study the dynamics of the genetic diversity  of oat va rieties at avenin-coding loci. For the analysis, 100 grains of each variety were used. Electrophoresis was  carried out in vertical plates of 13.2 % polyacrylamide gel at a constant vol tage of 500 V for 4.0–4.5 h. It was found  that 44.4 % of the varieties are heterogeneous, each consisting of two biotypes. For three loci, 20 alleles were  identified, 10 of which were detected for the first time. The allele frequency of avenin-coding loci varied with  time. In the process of variety exchange, alleles that are characteristic of varieties of non-Russian origin were replaced by alleles present in domestic varieties and then in the varieties developed by local breeding institutions.  The following alleles had the highest frequency in Tyumen varieties: Avn A4(50.0 %), A2(25.0 %), Avn B4(50.0 %),  Bnew6(37.5 %), Avn C1(37.5 %), C2 and C5(25.0 %). These alleles are of great value as markers of agronomically  and adaptively important characters for the region in question. The amount of genetic diversity of oats varied  with time from 0.33 in 1929–1950 to up to 0.75 in 2019. The high value of genetic diversity in modern breeding  varieties of the Scientific Research Institute of Agriculture of the Northern Trans-Urals and an increase in this  indicator over the past 20 years are associated with the use of genetically heterogeneous source material in the  breeding process. This allowed obtaining varieties with high adaptive potentials in the natural climatic conditions of the region.